THE ANALYSIS SERVICE QUALITY TOWARD CUSTOMER SATISFACTION OF GANUMBA TOUR & TRAVEL TELUKDALAM KABUPATEN NIAS SELATAN - Hendrik Kuasa Sihura (Jurnal Education and Development, 2019)
The objetive of this research is service quality toward customer Satisfaction Of Ganumba Tour & Travel Telukdalam Kabupaten Nias Selatan. This Researsh represent type research of survey that is research taking sample from a population using qusetoner as complier of the data. Data type the used id primary data which taken by questiner and secondary data which taken from the information report, referensi at Ganumba Tour & Travel Telukdalam Kabupaten Nias Selatan. Population ini this rsearch is all customers of Ganumba Tour & Travel Telukdalam Kabupaten Nias Selatan. Method intake of sample used accindental sampling taking amounting 100 respondents. Method analyzes data used is descriptive analysis with frequncy tabulation, mean, dan pencentage. The result of data amalysis show that: (1) the average perception value of realibility dimension on the 3,91 level (very satisfaction); (2) the average perception value of responsiveness dimension on the 3,90 level (very satisfaction); (3) the average perception value of assurance dimension on the 3,91 level (very satisfaction); (4) the average perception value of emphaty dimension on the 3,90 level ( very satisfaction); and (5) the average perception value of tangibles dimension on the 3,91 (very satisfaction).